Pembelajaran Praktis Shalat Jenazah Sebagai Sarana Memperdalam Pemahaman Agama - Setiawan, Ilham; Yahya Azzawiy, Amiruddin; Suzanna, Yenny (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2025)
Practical learning of funeral prayer has proven to be an effective method in deepening students' understanding of one of the fardhu kifayah obligations in Islam. This study aims to evaluate the extent to which learning the practice of funeral prayer can improve students' understanding at MTsS Terpadu Langsa. The method used in this research is a descriptive qualitative approach, where data is collected through observation, interviews, and documentation. The learning process combines lectures, discussions, and hands-on practice, where students are actively involved. The results showed that some methods, such as demonstration, simulation, and practical exercises, were able to significantly improve students' understanding. This is reflected in their ability to perform the procedures of the funeral prayer correctly and regularly. In addition, this learning also increases students' awareness of the importance of funeral preparation as part of social and religious responsibility. Based on these findings, this study recommends the application of hands-on learning in other religious materials to strengthen students' overall understanding.